Human rights in probation: theory, practice and balance - Hadjisergis, Kyros (Routledge frontiers of criminal justice, 2025)
"Exploring the application, theory, implications and socio-legal underpinnings of human rights in probation and associated offender management, this book examines the organisation and re-organization of the National Probation Service, from the introduction of the Human Rights Act (HRA) to the end of the Transforming Rehabilitation era. Outlining how the duties of probation officers are interpreted in light of the HRA, this book evaluates applicable case law as a means to exemplify and clarify the direct operation of human rights law in instances of potential human rights violations. Chapters also analyse the current and future infrastructure of probation to demonstrate challenges of awareness, implementation and compliance. Based on qualitative data analysed through a socio-legal lens and a human rights framework, themes explored include crime control and due process, and are reflective of the tensions and imbalances experienced between risk or public protection and human rights. The book also includes case studies of Serious Further Offences that have either shed light on the shortcomings in the area of human rights in probation or highlighted factors linked to human rights, including scapegoating, cumulative systemic failures, miscommunications and over-reliance on risk assessments. Finally, it provides clarity as to what the human rights duties of the Service are, what relevant laws apply alongside the HRA, and how these decisions affect risk and offender management. An important and timely study of probation in England and Wales, Human Rights in Probation will be of great interest to academics of probation, criminal justice, and human rights. It will also be of value to Probation officers (including trainees) and other practitioners working in offender management services"--